Subcritical water-carbon dioxide pretreatment of oil palm mesocarp fiber for xylooligosaccharide and glucose production - Ahmad, Norlailiza; Zakaria @ Mamat, Mohd Rafein; Mohd Yusoff, Mohd Zulkhairi; Fujimoto, Shinji; Inoue, Hiroyuki; Ariffin, Hidayah; Hassan, Mohd Ali; Shirai, Yoshihoto (MDPI, 2018)
The present work aimed to investigate the pretreatment of oil palm mesocarp fiber (OPMF) in subcritical H2O-CO2 at a temperature range from 150–200 °C and 20–180 min with CO2 pressure from 3–5 MPa. The pretreated solids and liquids from this process were separated by filtration and characterized. Xylooligosaccharides (XOs), sugar monomers, acids, furans and phenols in the pretreated liquids were analyzed by using HPLC. XOs with a degree of polymerization X2–X4 comprising xylobiose, xylotriose, xylotetraose were analyzed by using HPAEC-PAD. Enzymatic hydrolysis was performed on cellulose-rich pretreated solids to observe xylose and glucose production. An optimal condition for XOs production was achieved at 180 °C, 60 min, 3 MPa and the highest XOs obtained was 81.60 mg/g which corresponded to 36.59% of XOs yield from total xylan of OPMF. The highest xylose and glucose yields obtained from pretreated solids were 29.96% and 84.65%, respectively at cellulase loading of 10 FPU/g-substrate.